Mansonellosis at Medium Purus River (Brazilian Amazon) - DOI: 10.3395/reciis.v2i1.113en - Yara Leite Adami; Marilza Maia-Herzog (Instituto de Comunicação e Informação Científica e Tecnológica em Saúde (Icict) da Fundação Oswaldo Cruz (Fiocruz), 2008)
Mansonella ozzardi is a filarial autochthonous parasite of the American continent that is frequently found infecting human beings in the Brazilian Amazon. The human infection by M. ozzardi is still seen as non pathogenic despite the variety of symptoms related to it such as fever, articular pain, headache, lymphadenopathy, eosinophily and pruritic skins eruptions. During an expedition in the Acre State, we were able to visit the Kamikuã, an Indian village located along the Purus river, close to the city of Boca do Acre (Amazonas State). The inhabitants had been diagnosed as harboring dog´s worms (Dirofilaria immitis) but our blood samples collections from some individuals evidenced M. ozzardi infections. In fact, human populations from endemic areas are always complaining about symptoms of M. ozzardi infection and remain living together with high parasitic loads in the expectation of correct diagnostic and treatment. Studies on mansonellosis chemotherapy and control should be carried out in order to add knowledge about the infection and to provide hope and answers for those who live in endemic areas.